Platinum catalysts supported on MWNT for catalytic wet air oxidation of nitrogen containing compounds - García, Juan (2009)
Multi-walled carbon nanotubes (MWNT) activated by nitric acid oxidation were used to prepare supported platinum (1% Pt) catalysts by the excess solution impregnation method. Three different platinum precursors were used to prepare the impregnation solutions, namely diiodo dicarbonyl platinum(II) [PtI2(CO)2], dimethyl (1,5-cyclooctadiene) platinum(II) [Pt(CH3)2(C8H12)] and hydrogen hexachloroplatinate(IV) hexahydrate H2PtCl6 6H2O. The catalysts were characterized by transmission electron microscopy (TEM) analysis and H2 chemisorption. They were tested in the catalytic wet air oxidation (CWAO) of aniline aqueous solutions (200 8C and 6.9 bar of oxygen partial pressure). The Pt/MWNT catalyst prepared from H2PtCl6 6H2O showed the best performance with respect to combined activity and selectivity for aniline conversion to non-organic compounds. This catalyst was used in CWAO (150 8C and 6.9 bar of oxygen partial pressure) of aqueous solutions of various textile dyes such as the monoazo dye chromotrop 2R (C2R), the diazo dye erionyl red B (ERB) and the triazo dye solophenyl green BLE (SG) 155%. It was found that the selectivity for dye removal decreased in the order diazo > monoazo > triazo. The CWAO of a textile wastewater was also performed using the same catalyst and identical reaction conditions. Complete color removal and 51.2% TOC abatement was obtained under these conditions.